Immunohistochemical Study of Cancer Stem Cell marker, Tight Junction Protein, and Lymphatic Density in Malignant Salivary Gland Tumors - Maghrabi, Marwa; Farag, Doaa A.; Shakweer, Marwa; Negm, Mohamed; El-Sissy, Nadia A. (Open Access Macedonian Journal of Medical Sciences, 2022)
Background: CD117/c-kit, is a powerful stem cell marker for malignant salivary gland tumors in which dysregulation of c-kit is closely associated with impairment of cell adhesion molecules and cancer metastasis. Objective: The main purpose of this work is to evaluate the immunohistochemical expression of c-kit, and claudin-1 and measure the density of lymph vessels (LVD) in common malignant salivary gland tumors by using podoplanin (D2-40) antibody. Materials and Methods: Immunohistochemical staining with streptavidin peroxidase was used to analysis the expression of c-kit, claudin-1 and stained podoplanin (D2-40) lymphatic vessels on fifty archival paraffin blocks of malignant salivary gland tumor (MSGTs) cases included 20 cases of AdCC, 11 cases of MEC, 10 cases of CXPA, 6 cases of AcCC, and 3 cases of PAC. Results: The immunopositivity of c-kit (CD117) was detected in 44/50 (88%) of studied cases, whereas, claudin-1 protein was observed in 35 (70%) of our specimens of MSGTs. Count down of stained lymph vessels between examined cases was, MEC on the top, followed by CXPA, AdCC, PAC and AcCC. A direct correlation was observed between c-kit and lymphatic density, on the other hand, the inverse correlation was found d between c-kit and cld-1, as well as, between cld-1 and lymphatic density Conclusion: Up regulation of cancer stem cell marker c-kit (CD117) expression is associated with decrease of tight junction protein cld-1 and increase the density of stained lymphatic vessels by podoplanin (D2-40) antibody which confirms the using of c-kit inhibitor to improve treatment strategy of malignant salivary gland tumors.